Faktor-Faktor Yang Melatarbelakangi Pembentukan Identitas Diri Pad a Remaja Transgender Di Perkumpulan Yotha Naungan PKBI DIY - Maria Nataliani Novatsiana Lagut, Sri Hendarsih, Christin Wiyani (Universitas Respati Yogyakarta, 2016)
Background : of identity may be influenced several idol, and experience ofsocial Lack ofsupport from these factors cause deviation in the formation self identity as experienced by transgender teens. Objective' To identify the factors which influence the formation of self identity on transgender teens. Research method . This research was conducted at Yotha association under the of PKBI Yogyakarta. It qualitative phenomenological design by interviewing 3 infromants. Result· The discort between transgender teen and his father as well as the absence of atherbecause he did not assume his responsibility rearing after divorce has made his oedipus